Holocene environment of Central Kamchatka, Russia: Implications from a multi-proxy record of Two-Yurts Lake - Hoff, Ulrike; Biskaborn, Boris (Prof.); Dirksen, Veronika G.; Dirksen, Oleg; Kuhn, Gerhard; Meyer, Hanno; Nazarova, Larisa B. (Dr.); Roth, Alexandra; Diekmann, Bernhard (PD Dr. habil.) (Global and Planetary Change, 2015)
Within the scope of Russian German palaeoenvironmental research, Two-Yurts Lake (TYL, Dvuh-Yurtochnoe in Russian) was chosen as the main scientific target area to decipher Holocene climate variability on Kamchatka. The 5 x 2 km large and 26 m deep lake is of proglacial origin and situated on the eastern flank of Sredinny Ridge at the northwestern end of the Central Kamchatka Valley, outside the direct influence of active volcanism. Here, we present results of a multi-proxy study on sediment cores, spanning about the last 7000 years. The general tenor of the TYL record is an increase in continentality and winter snow cover in conjunction with a decrease in temperature, humidity, and biological productivity after 5000-4500 cal yrs BP, inferred from pollen and diatom data and the isotopic composition of organic carbon. The TYL proxy data also show that the late Holocene was punctuated by two colder spells, roughly between 4500 and 3500 cal yrs BP and between 1000 and 200 cal yrs BP, as local expressions of the Neoglacial and Little Ice Age, respectively. These environmental changes can be regarded as direct and indirect responses to climate change, as also demonstrated by other records in the regional terrestrial and marine realm. Long-term climate deterioration was driven by decreasing insolation, while the short-term climate excursions are best explained by local climatic processes. The latter affect the configuration of atmospheric pressure systems that control the sources as well as the temperature and moisture of air masses reaching Kamchatka. (C) 2015 Elsevier B.V. All rights reserved.